HEMODYNAMIC INDEXES DYNAMICS IN ACTIVITY OF ENDOTHELIUM IN REPLY TO VELOERGOMETRY IN PATIENTS WITH ARTERIAL HYPERTENSION - Sirik, V.О. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
104 patients with arterial hypertension were inspected. Estimation of patients well-being, clinical criteria of arterial hypertension, interleukin-8, endothelin, E-selectin, veloergometry, EKG was conducted. The obtained results were estimated by statistical methods. It is determine, that strengthening of endothelial dysfunction in reply to veloergometry is related to development of pathological changes in endothelium which come at progression of of arterial hypertension. As a criterion of prognostication of further development of arterial hypertension comparison of types of reaction of hemodynamics on the exercise stress with estimation of endothelium activity can be chosen.